Fulfillment of the Health Rights of Persons with Disabilities - Dumako, Ananda Rayhan (CV. Rayyan Dwi Bharata, 2024)
Indonesia has ratified the Convention on the Rights of Persons with Disabilities (CRPD) and regulates the right to health services through Law Number 8 of 2016, but there are still challenges in ensuring equal access for people with disabilities in Indonesia. Lack of accessibility of health facilities and discrimination faced by people with disabilities. Using normative legal research methods and statutory provision approaches, this article examines how persons with disabilities can exercise their rights and how the Government of Indonesia implements policies to protect the rights of persons with disabilities. The results show that despite legal protection efforts, gaps still exist in terms of physical accessibility and health services for people with disabilities. Many facilities do not meet accessibility standards, and medical personnel's understanding of the rights of people with disabilities is still limited. Even though several regulations in Indonesia emphasize equal access to health services, much attention is still paid to the issue of physical accessibility, inadequate information, and lack of understanding and awareness on the part of healthcare providers. To achieve equal access for people with disabilities, it is necessary to strengthen legal protection and implement policies and concrete steps in improving facilities, information, and education for health workers.